AUSTRALIAN FOREIGN AID MOTIVATION FOR TUVALU IN EFFORTS TO COPE WITH CLIMATE CHANGE 2015 - 2020 - Hallatu, Farah Diba; Indrayani, Irma (Journal of Social Political Sciences, 2022)
Tuvalu is a country located in the Pacific Region which only has an area of about 26 square kilometers with an average height of only 1.83 meters which makes this country very vulnerable to the impacts of climate change, especially sea level rise. Tuvalu is quite dependent on foreign aid from donor countries. Australia is one of the most disaster-responsive countries and continues to assist Tuvalu in its efforts to deal with the impacts of climate change. In trying to understand Australia's background in providing assistance, the approach used is a qualitative method through literature study. The theories used to answer this phenomenon are the theory of foreign aid, the theory of soft power, and green political theory. Based on the data analysis, it was concluded that Australia has a low commitment to climate change and has not taken the right steps to achieve climate targets, so that the foreign assistance provided by Australia is one of Australia's soft power strategies to maintain its dominance and influence in the Pacific Region. Australia can form a defense and security mapping to protect its national interests. Although the countries in the Pacific Region are relatively small and of little significance, Australia is taking advantage of the situation by making living fences as far as possible.